Analysis of Components Selection of Oil Draining Machine for Spinner System Based Analytical Hierarchy Process - Evander Simanjuntak; Anita Susilawati; Herisiswanto Herisiswanto; Dedi Rosa Putra Cupu (Journal of Ocean, Mechanical and Aerospace -science and engineering-, 2023)
The function of the oil draining machine is to effectively reduce the oil content in the food from frying. This study aims to analyse the spinner system's components for the oil draining machine using the Analytical Hierarchy Process (AHP) method. The AHP makes broad and unstructured problems into a flexible and easy-to-understand model. This research begins with a study of the initial design of the spinner system for the oil-draining machine components. Then, the characteristics and process parameters (spinner) of the oil-draining machine's parts were analysed using the AHP method. From the analysis results, the new designs were developed by eliminating or combining components that did not add value. The priority of consumer needs for function, performance, ergonomics, durability, serviceability and aesthetics were referenced to make a new design. Then, the new components of the spinner system oil draining machine were developed. Customers' needs for design priority include functionality to drain the cooking oil and crackers, capacity exceeding 3kg, ease of assembly, lightweight, easy to use, stainless steel material, easy to repair and dark colour selection.